Carbon assisted growth and photoluminescence of silicon nanowires fabricated without a catalyst - Al-Ruqeishi, M.S.; Nor, R.M.; Amin, Y.M.; Al-Azri, K. (2010)
One-dimensional (1D) silicon nanowires (SiNWs) were fabricated on a catalyst free Si (100) substrate using a thermal evaporation method. Based on a SVLS growth mechanism, the SiNWs obtained were 30-265 nm in diameter and 1.7 mu m to several tens of microns in length. It was found that the presence of graphite powder alone is enough to accomplish the growth. A systematic study of how the growth conditions, such as the Ar carrier gas flow rate, and the growth time effect was performed. The Photoluminescence (PL) of SiNWs was also investigated. The observed broad band is composed of an UV peak or band centered at 350 nm (3.54 eV) and a wide hemisphere curve over the green bluish region (430-550 nm). The theory behind these emissions is discussed.